Polyphyllin VI induces apoptosis and autophagy in human osteosarcoma cells by modulation of ROS/JNK activation - Yuan YL; Jiang N; Li ZY; Song ZZ; Yang ZH; Xue WH; Zhang XJ; Du Y (Dove Medical Press, 2019)
Yong-Liang Yuan,1,* Neng Jiang,2,* Ze-Yun Li,1 Zhi-Zhen Song,1 Zhi-Heng Yang,1 Wen-Hua Xue,1 Xiao-Jian Zhang,1 Yue Du11Department of Pharmacy, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan, People’s Republic of China; 2Department of Pharmacy, The Affiliated Tumor Hospital of Guangxi Medical University, Nanning, Guangxi 530021, People’s Republic of ChinaCorrespondence: Yong-Liang Yuan; Yue DuDepartment of Pharmacy, The First Affiliated Hospital of Zhengzhou University, Jianshe East Road 1, Zhengzhou, Henan 450052, People’s Republic of ChinaTel/fax +86 03 716 629 5651Email yylcpu@126.com; fccduy@zzu.edu.cn*These authors contributed equally to this workPurpose: Polyphyllin VI, a main active saponin isolated from traditional medicinal plant Paris polyphylla, has exhibited antitumor activities in several cancer cell lines. In the present study, we investigated the antitumor effect of Polyphyllin VI against human osteosarcoma cells (U2OS) and the underlying molecular mechanisms.Methods: The U2OS cell lines were used to determine the antiproliferative effect of Polyphyllin VI by CCK8 assay. Cell cycle was analyzed by flow cytometry. The Polyphyllin VI-induced apoptosis was determined by Annexin V-APC/7-AAD apoptosis detection kit and JC-1 staining. Meanwhile, the autophagy was determined by acridine orange staining. The apoptosis and autophagy-related proteins were monitored by Western blot assay. Subsequently, intracellular hydrogen peroxide (H2O2) and the activation of ROS/JNK pathway were detected.Results: Polyphyllin VI could potently inhibit cell proliferation by causing G2/M phase arrest. Polyphyllin VI induced mitochondria-mediated apoptosis with the upregulation of proapoptotic proteins Bax and poly ADP-ribose polymerase, and downregulation of antiapoptotic protein Bcl-2 in U2OS cells. Concomitantly, Polyphyllin VI provoked autophagy with the upregulation of critical Atg proteins and accumulation of LC3B-II. Intracellular H2O2 production was triggered upon exposure to Polyphyllin VI, which could be blocked by ROS scavenger. Polyphyllin VI dramatically promoted JNK phosphorylation, whereas it decreased the levels of phospho-p38 and ERK.Conclusion: Our results reveal that Polyphyllin VI may effectively induce apoptosis and autophagy to suppress cell growth via ROS/JNK activation in U2OS cells, suggesting that Polyphyllin VI is a potential drug candidate for the treatment of osteosarcomas.Keywords: Polyphyllin VI, osteosarcoma, apoptosis, autophagy, JNK activation